Clinical features of fallopian tube accessory ostium and outcomes after laparoscopic treatment. Issue 3 (1st March 2015) - Zheng, Xingbang; Han, Hongjing; Guan, Jing
Abstract: Objective: To investigate the clinical features of fallopian tube accessory ostium and treatment outcomes after laparoscopic treatment. Methods: A retrospective analysis was conducted of patients who underwent laparoscopy for infertility at Peking University People's Hospital, Beijing, China, between June 1, 2009, and January 31, 2012. Fallopian tube accessory ostium was treated surgically when identified. Other procedures were conducted simultaneously, if indicated. Patients were interviewed by telephone every 6 months after treatment. Results: Among 1113 patients who underwent laparoscopy for infertility, 21 (1.9%) were diagnosed with fallopian tube accessory ostium. Furthermore, 19 (90.5%) of these 21 women were diagnosed with pelvic endometriosis. Accessory ostium was identified in 19 (4.7%) of 403 women with endometriosis versus 2 (0.3%) of 710 women without endometriosis ( P = 0.001). Among 18 patients with accessory ostium who completed follow‐up and wished to conceive, 12 (66.7%) conceived after surgery, one of whom experienced a spontaneous abortion. No ectopic pregnancies occurred. Conclusion: Accessory ostium was confirmed by a thorough examination of the entire fallopian tube, especially the distal portion, during laparoscopy. Patients experienced satisfactory outcomes after surgical intervention.